Packaging development for the storage and logistical transport of auto parts: a bibliometric study (Research, Society and Development, 2023)
The automobile industry is considered a very important sector in the economy of several countries, including being studied by many researchers and specialists in the area. However, despite the studies focused on the sector, few are focused on the packaging development process for the transport and storage of auto parts. Faced with this gap, this research carried out a bibliometric survey in order to identify research trends about scientific publications related to the central theme of this work, which is the development of packaging for the transport of auto parts used in the vehicle assembly process. For this, the bibliometric data were obtained through consultations with the scientific databases Scopus and Web of Science, which, after being extracted, were compiled in an electronic spreadsheet. These data were analyzed in the light of the research topic, where only documents that were related were selected. Then, the results obtained by the bibliometric analysis were illustrated in the form of tables, graphs and figures, which, when analyzed, point out what has already been studied and current research trends. Finally, the study identified a certain incipience in relation to the amount of scientific research carried out, despite the growth in the number of publications over the last few years. This fact justifies the development of this work, which aims to be a starting point for the development of future research.